Outcome of 20% topical zinc oxide ointment in the treatment of cutaneous warts of hands and feet - Arshad, Atiya; Younas, Sana; Ahmed, Tahir Jamil; Rashid, Tariq; Nadeem, Muhammad (Journal of Fatima Jinnah Medical University, 2019)
Background: Viral warts (verrucae) are benign proliferations of skin and mucosa that result from different types of human papilloma viruses (HPVS). Warts may occur at any age, but they are more common in children and adolescents. Various treatment modalities are available for warts, but none is uniformly effective. Ultimate treatment often includes destructive measures, which are usually painful and carry risk of scarring. This study aims to find out the treatment outcome of 20% topical zinc oxide treatment of cutaneous viral warts of hands and feet, as zinc oxide is cheap and easy to apply. Patients and methods: This is a prospective descriptive analytical study conducted at the Outpatient Department (OPD) of Dermatology, Sir Ganga Ram Hospital, Lahore from December 2013 to June 2014. Two hundred and fiftyfive (255) patients were enrolled and instructed to apply topical 20% Zinc Oxide Ointment twice daily. Patients were followed fortnightly for a period of 3 months or till complete cure, whichever occurred first. Results: Out of total 255 patients, 173 (67.8%) were female, and 82 (32.2%) were male. The mean age of patients was 17.55±4.48 years. Complete cure was observed in 127 (49.8%) patients at the end of 3 months of treatment, 41 (16.1%) showed a moderate response while 35 (13.7%) Conclusion: Topical Zinc Oxide (20%) Ointment may be considered an effective and safe initial treatment for cutaneous warts of hands and feet.